Penerapan Fiqih Muamalah Sebagai Dasar Kewenangan Pengadilan Agama Dalam Penyelesaian Sengketa Ekonomi Syariah - Renny Supriyatni (Syiar Hukum, 2010)
he development of Islamic economic institutions in Indonesia has created the conflict of interest between  stakeholder and  Religious Court, especially in settlement of syariah-economic disputes. The  application of fiqih muamalah in settlement of syariah-economic disputes in Islamic Religious Court,  has been the crucial issue in Indonesia positive law . This article will seek to find and determine  whether the application of  fiqih muamalah as a basis in such dispute settlement is consistent with  the Islamic Law Principles. It also examines the implementation of  fikih muamalah that has become an Indonesian postive law. This research applies juridical normative approach.  Data collection  is gathered from library research complemented by primary from field research. The specification of this research is descriptive analysis, and the data gathered  is analyzed in qualitative method.  The article will demonstrate that  the above fiqih muamalah rules are stipulated in Law No.3 of 2006  Jo. Law No 50 of 2009 on  Second Amendment of Act No.7 of 1989.  Meanwhile, the Islamic Law Principles have been adopted by Law No.21 of 2008,  the Supremre Court Decree No 2 of 2008 and other relevant laws and regulations. The author  recommends that the Indonesian Government adopt implementing regulation on syariah- economic.  It is also recommended that the government  should enhance socialization of the laws and regulations relating to fikih muamalah and syariah –economic  to the general public.   This can be a  guidance for the Indonesian Muslims to comprehensively practice  their religion teaching.